Pituranthos chloranthus Oil as an Antioxidant-Based Adjuvant Therapy against Cisplatin-Induced Nephrotoxicity - Aida Lahmar; Zaineb Dhaouefi; Rihab Khlifi; Fairouz Sioud; Leila Chekir- Ghedira (Journal of Toxicology)
The therapeutic outcome of cisplatin is limited due to its adverse side effects in normal tissues. Despite its potent antineoplastic effect, cisplatin is known by a relevant collateral action, for instance, acute renal failure. The aim of this study was to assess the effectiveness of Pituranthos chloranthus (PC) essential oil for contracting cisplatin-induced toxicity, in Balb/c mice. The standard mouse model of cisplatin-induced acute kidney injury (AKI), consisting of one intraperitoneal injection of cisplatin (20 mg/kg), was adopted. Mice were pretreated by intraperitoneal administration of PC (5 and 10 mg/Kg b.w) for one week. Cisplatin induced alteration in renal and liver functions, evidenced by increased serum biomarkers levels (creatinine, ALT, and AST). Significant mitigation of cisplatin-induced toxicity was confirmed by lowered levels of serum biomarkers and reduced DNA damage in liver and kidney. PC also restored the alterations in oxidative stress markers and proinflammatory cytokine IFN-γ level. Overall, this study provides, for the first time, that PC can be applied as an antioxidant-adjuvant treatment to mitigate cisplatin-induced renal failure.